Key Trends in Changes to Primary Education in the Czech Republic after the 1989 Velvet Revolution - Spilková, Vladimíra (My University, 2024)
The aim of the review study is to reflect on key trends in the process of transformation of primary education in the Czech Republic after the 1989 Velvet Revolution. The major milestones in the transformation process in terms of education policy are reflected upon. The core of the study is an analysis of the key theoretical foundations of transformation and the changes to primary education in the reality of school practice, including the most significant innovative approaches. The study concludes with an evaluation of the overall development of Czech primary education after 1989 in the context of international trends and with reflection on the prospects for its further development.
Klíčové trendy v proměnách základního vzdělávání v České republice po sametové revoluci 1989
Keywords: primary education; transformation; education policy; základní školství; transformace; vzdělávací politika